2022
DOI: 10.1002/ejhf.2482
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic profiling of supranormal ejection fraction reveals decreased survival and underdiagnosed heart failure

Abstract: Individuals with supranormal left ventricular ejection fraction (snLVEF; LVEF >70%) have increased mortality. However, the genetic and phenotypic profile of snLVEF remains unknown. This study aimed to determine the relationship of both snLVEF genetic risk and phenotype with survival and underdiagnosed heart failure (HF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Remarkably, patients with a normal LVEF while showing the lowest risk for the primary outcome of HF hospitalization and all-cause mortality had the highest rate of previous HF hospitalizations and the most patients in NYHA Class IV compared to other subgroups. This could be caused by a general underdiagnosis of heart failure in patients with normal LVEF, thus only patients with really severe heart failure symptoms and a high burden of disease get diagnosed with it at a later stage and were therefore more often treated in the hospital previously [26,27]. In addition, the differentiated profile of these patients might raise the question of whether they are typical heart failure patients or whether they suffer from another underlying related condition.…”
Section: Outcomementioning
confidence: 99%
“…Remarkably, patients with a normal LVEF while showing the lowest risk for the primary outcome of HF hospitalization and all-cause mortality had the highest rate of previous HF hospitalizations and the most patients in NYHA Class IV compared to other subgroups. This could be caused by a general underdiagnosis of heart failure in patients with normal LVEF, thus only patients with really severe heart failure symptoms and a high burden of disease get diagnosed with it at a later stage and were therefore more often treated in the hospital previously [26,27]. In addition, the differentiated profile of these patients might raise the question of whether they are typical heart failure patients or whether they suffer from another underlying related condition.…”
Section: Outcomementioning
confidence: 99%
“…The relationship between LVEF and mortality may be U-shaped with an increased risk also for patients with a LVEF >65-70%, so-called HF with supranormal LVEF (HFsnLVEF). 9,10 Forrest et al 11 investigated the implications of genetic and phenotypic profiles of a LVEF >70% in 486 754 individuals, across two population-based cohorts. They found that the predisposition to and the presence of LVEF >70% had a negative impact on survival and might lead to underdiagnosed HF.…”
Section: Imagingmentioning
confidence: 99%
“…Forrest and colleagues exploited all this previous knowledge on polygenic heritability of common cardiac disease to perform the first GWAS on the new category of snLVEF patients 6 . These analyses were performed across two large population‐based cohorts (UK Biobank – mainly healthy volunteers – and BioMe Biobank – mainly outpatients).…”
mentioning
confidence: 99%
“…In this study, 6 clinical phenotypes were obtained from electronic records. The authors acknowledged this as the main limitation, which is intrinsic to epidemiological studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation